Copper and molybdenum supplementation to sheep in the Sourveld of the Eastern Cape Province - Bishop, E. J. B.(Edward John Bassett) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. (Agric.)) -- University of Stellenbosch, 1957.